DEPRESSION IN ADOLESCENTS AND PSYCHOLOGICAL FACTORS - Kahveci, Muedin; Bolcal, Derya; Çelik, Ilhan (International Scientific Journal Vision, 2024)
The adolescence period, which is the period after childhood, is when the individual experiences rapid physical and mental changes. Adolescents are trying to adapt to the changes they have experienced, to their environment and family. With the effect of adolescence, his voice, appearance, and sexual difference change. It gets out of concrete periods and gains an abstract point of view. During this period, the adolescent attaches importance to his independence and freedom and falls into depression when he does not receive sufficient support from the family or society. During this period, the adolescent is to create his own identity. His ideas are changing daily, and he is constantly searching for discovery. This situation mentally exhausts the adolescent himself and shows depressive symptoms. Adolescence consists of three phases: early, middle, and late adolescence. (Koç, 2004). Adolescents are in rapid growth. Early adolescence covers the ages of 12-14. In the process of sexual development, girls begin earlier than boys; these developmental processes are positively affected by boys, while girls suffer from eating disorders and depression due to low self-perception.